Intimate Partner Relationship, Coping Strategies and Somatic Symptoms in Married Women (Journal of Social Sciences Review, 2025)
The present study examined the relationship between intimate partner relationships, coping strategies, and somatic symptoms in married women. A correlational research design was used in the research, with a total sample size of N=200 married women. Snowball sampling was used to gather data from married women. Standardized tools measured relationship quality, somatic symptoms, and coping styles, including emotion-focused and problem-focused coping. The results indicated that poor relationship quality was significantly associated with increased somatic complaints or symptoms in married women. Emotion-focused coping was positively correlated with higher somatic complaints, while problem-focused coping showed a negative relationship, indicating its protective role. Furthermore, dyadic coping partially mediated the link between relationship quality and somatic symptoms. Group comparisons revealed that unemployed women reported significantly more somatic symptoms than employed women. Similarly, women from nuclear families showed higher levels of somatic symptoms compared to those from joint family systems. These findings emphasize the psychosomatic impact of relationship stress and coping style and suggest the need for low-cost, culturally sensitive couple-based interventions for married women. Implications can be done in future for further guideline and clinical purpose.
Keywords: Intimate Partner Relationships; Coping Strategies; Emotion-Focused Coping; Problem-Focused Coping; Somatic Symptoms; Dyadic Coping; Family Structure; Employment Status